The role of trumpet musical aesthetics in Movement II of Bandung marching band: An analysis in “Bandung 1946” - Andios Resiok Topa; Davin Permana Putra (Interlude: Indonesian Journal of Music Research, Development, and Technology, 2023)
This study examines the influence of trumpet musical aesthetics in Movement II of the Bandung Marching Band "Bandung 1946," emphasizing the deep correlation between visual and auditory components, historical backdrop, and cultural importance. The focus of this inquiry is the trumpet's capacity to augment a performance's impact through its visual presentation, ornamentation, and symbolic associations with tenacity and defiance, which are rooted in Indonesia's war for independence. The significance of this research is in comprehending how the trumpet's musical aesthetics enhance the total experience and emotional impact of the performance, guaranteeing that the legacy of "Bandung 1946" persists in inspiring and captivating audiences. A descriptive qualitative method was utilized to analyze this musical work's intricate and culturally rich nature. This method entails methodically gathering, arranging, and explaining data while capturing descriptive information through verbal or written language and observable behaviours. The research methodology employed observations and document analysis to collect extensive data on the trumpet's aesthetic and cultural importance. The findings demonstrate that the trumpet's precise synchronization with the music's rhythm and dynamics, strategic embellishments, and historical and cultural symbolism greatly enhance the performance. The combination of visual and audio elements in this synthesis results in a compelling and captivating experience that pays tribute to Indonesia's heritage and enhances its cultural narrative. The descriptive qualitative method successfully captured the intricate and subtle role of the trumpet, showcasing its significance in attaining a powerful and meaningful performance. This study emphasizes the crucial significance of musical aesthetics in establishing a connection between audiences and cultural and historical narratives through performance.